Feed for feeding crabs - LI CHUNLIN; BAO TENGFEI; CHU LAIQUAN (2016)
The invention provides a feed for feeding crabs, and relates to the technical field of domestic feeding of aquatic products. The feed is characterized by being prepared from the following materials in parts by weight: 5 parts of calcium gluconate, 5 parts of sodium citrate, 5 parts of dried black carp powder, 1 part of gourmet powder, 5 parts of rose flowers, 4 parts of dry chrysanthemum flowers, 4 parts of green tea leaves, 4 parts of mung beans, 5 parts of soybeans, 4 parts of cooked duck yolk, 5 parts of cattle gristle, 2 parts of hot red peppers, 4 parts of carrot dices, 3 parts of coccinella septempunctata, 4 parts of pitaya peel, and 6 parts of a conditioning agent. The method disclosed by the invention is reasonable, convenient to operate and reasonable in compounding ratio. 种螃蟹喂养的料，涉及水产家养技术领域，其特征在于：由以下重量份的材料制成，葡萄糖酸钙5份、柠檬酸钠5份、青鱼干粉5份、味精1份、玫瑰花5份、干菊花4份、绿茶叶4份、绿豆4份、黄豆5份、熟鸭蛋黄4份、牛脆骨5份、红椒2份、胡萝卜块4份、七星瓢虫3份、火龙果皮4份、调理剂6份。本发明方法合理、操作方便、配比合理。